The role of behavior-related comments in parent–child interactions with the digital audio learning system Tiptoi® - Wildt, Eugenia (Frontiers in Developmental Psychology, 2024)
Whereas previous research has investigated shared reading of both print and digital storybooks, it has paid little attention to hybrid storybook reading. This study aims to address two gaps in the existing literature. First, we investigate the use of a hybrid reading medium, specifically Tiptoi®, in the Digital Home Literacy Environment (DHLE) of 40 preschoolers and first graders. Second, we examine parental comments during shared storybook reading, focusing particularly on the purpose of behavioral comments. Results indicate that children aged 4-7 years use Tiptoi® regularly and mostly independently. For parent-child interactions, we found that parents spend about one-half of the reading interaction time on book-related content and one-third on behavior-related talk. Behavior-related comments were used to provide instructions, to structure the interaction, and to address the technology itself. Overall, our study provides valuable insights into the use of the digital audio learning system Tiptoi® in children's DHLE, and it highlights the importance of parental behavioral comments in supporting the practice of reading with hybrid storybooks.